Techno-economic assessment of integrated hydrochar and high-grade activated carbon production for electricity generation and storage. (August 2017) - Kempegowda, Rajesh S.; Tran, Khanh-Quang; Skreiberg, Øyvind
Abstract: This paper deals with process simulation and techno-economic assessment on a bioenergy system for sustainable electricity production from low-grade biomass resources such as forest and agricultural residues, which is suitable for rural areas in developing regions susceptible to intermittent electricity supply. The core of the system is hydrothermal carbonization of wet biomass for production of hydrochar, followed by wet milling and direct combustion of the obtained hydrochar slurry fuels for heat and power generation. In order to improve the economy and make the process a closed-loop system, the paper also identifies a bio-refining strategy focusing on production of high-grade activated carbons for energy storage using supercapacitor. Aspen Plus software package is used as simulation and optimization tool. The result shows that the proposed system is highly feasible both technically and economically. The cost of electricity varies from 0.2 to 0.4 $/kWh in the efficiency range of (40 % to 20 %), which depends on the hydrothermal carbonization operating conditions.